An assessment of the real-world driving gaseous emissions from a Euro 6 light-duty diesel vehicle using a portable emissions measurement system (PEMS). (February 2018) - Luján, José M.; Bermúdez, Vicente; Dolz, Vicente; Monsalve-Serrano, Javier
Abstract: Recent investigations demonstrated that real-world emissions usually exceed the levels achieved in the laboratory based type approval processes. By means of on-board emissions measurements, it has been shown that nitrogen oxides emitted by diesel engines substantially exceed the limit imposed by the Euro 6 regulation. Thus, with the aim of complementing the worldwide harmonized light vehicles test cycle, the real driving emissions cycle will be introduced after 1 September 2017 to regulate the vehicle emissions in real-world driving situations. This paper presents on-board gaseous emissions measurements from a Euro 6 light-duty diesel vehicle in a real-world driving route using a portable emissions measurement system. The test route characteristics follow the requirements imposed by the RDE regulation. The analysis of the raw emissions results suggests that the greatest amount of nitrogen oxides and nitrogen dioxide are emitted during the urban section of the test route, confirming that lower speeds with more accelerations and decelerations lead to higher nitrogen oxides emissions levels than constant high speeds. Moreover, the comparison of the two calculation methods proposed by the real driving emissions regulation has revealed emissions rates differences ranging from 10% to 45% depending on the pollutant emission and the trip section considered (urban or total). Thus, the nitrogen oxides emissions conformity factor slightly varies from one method to the other. Highlights: Accelerations at low speeds lead to higher NOx emissions than constant high speeds. HC and CO emissions rates are driven by the levels emitted in the motorway section. 10%–45% difference between both analytical methods depending on the pollutant emission. The trip NOx conformity factor was 2.61 (first method) and 2.35 (second method). Strong, moderate and low impact of cold start on CO, HC and NOx levels, respectively.